Changes in BMI and physical activity from youth to adulthood distinguish normal-weight, metabolically obese adults from those who remain healthy - Viitasalo, A.; Pahkala, K.; Lehtimäki, T.; Viikari, JSA.; Tammelin, TH.; Raitakari, O.; Kilpeläinen, TO. (Frontiers in Endocrinology, 2022)
Background: Individuals with metabolically obese normal-weight (MONW) have higher risk of cardiovascular events than those with obesity but a metabolically healthy status. Etiological factors leading to MONW are not well known. We hypothesized distinct trajectories of changes in BMI and physical activity may modify metabolic risk and distinguish individuals with MONW from those who remain healthy. Methods: We compared the mean levels of BMI and physical activity at eight time points (1980, 1983, 1986, 1989, 1992, 2001, 2007, 2011) between MONW and healthy normal-weight adults using linear mixed-model analysis. The analyses included 1180 participants of the Cardiovascular Risk in Young Finns study, a population-based study that represents six different age cohorts 3, 6, 9, 12, 15 and 18 years of age at baseline. Results: Individuals with adult MONW had significantly lower BMI in childhood and young adulthood, but their BMI increased more than in other adults after this age (p<0.001for interaction between time and MONW status). Physical activity decreased relatively more since youth in individuals with adult MONW (p<0.001). Conclusions: Relative leanness in youth and subsequent weight gain in young adulthood, and a gradual decrease in physical activity levels from youth to adulthood, predispose normal-weight individuals to metabolic impairments. The results highlight the importance of a healthy lifestyle in the prevention of metabolic disorders, particularly in individuals who are slim in childhood.